White-Matter Repair as a Novel Therapeutic Target for Early Adversity - Islam, Rafiad; Kaffman, Arie (Frontiers in Neuroscience, 2021)
Early adversity (EA) impairs myelin development in a manner that persists later in life across diverse mammalian species including humans, non-human primates, and rodents. These observations, coupled with the highly conserved nature of myelin development suggest that animal models can provide important insights into the molecular mechanisms by which EA impairs myelin development later in life and the impact of these changes on network connectivity, cognition, and behavior. However, this area of translational research has received relatively little attention and no comprehensive review is currently available to address these issues. This is particularly important given some recent mechanistic studies in rodents and the availability of new agents to increase myelination. The goals of this review are to highlight the need for additional pre-clinical work in this area and to provide specific examples that demonstrate the potential of this work to generate novel therapeutic interventions that are highly needed.